The production and financial achievement of the agricultural co-operatives in 2002-2007 - Harangi-Rákos, Mónika (Acta Agraria Debreceniensis, 2012)
The aim of the study was the examination of the achievement of the Hungarian agricultural enterprises – special regard to the agricultural co-operatives – based on the aggregated database of Hungarian Tax and Financial Control Administration (APEH), from the database of the Research Institute of Agricultural Economics. From the methodological aspect plain statistical devices were used, indicators for corporate analyses werecalculated and analyzed for the time series. One important conclusion is that the socio-economic weight of the agricultural co-operatives was strongly decreased in the period after the EU accession. The other important statement is that over the general examination of economic actors on an aggregated level the comparative analysis of the single enterprises forms would be needed. In the case of the co-operatives the separated examination of the former type producer co-operatives and the new type co-operatives would be necessary